Use of the Long and Short Forms of the Depression in the Medically Ill Questionnaire in a Spanish Population. (August 2013) - Orive, Miren; Padierna, Jesús A.; Las Hayas, Carlota; Vrotsou, Kalliopi; Quintana, Jose M.
This study sought to translate, using a back-translation procedure, and evaluate the psychometric characteristics of Depression in the Medically Ill questionnaire (DMI-18) and its short version (DMI-10) in a Spanish population. Patients with somatic disorders ( N = 366) completed the translated DMI-18 and another depression questionnaire. Among these, 167 were also assessed by a mental health professional (gold standard) to test criterion validity. Furthermore, coefficient alpha for both the versions were high (>.90), and convergent validity assessed against the Beck Depression Inventory for Primary Care, the Hospital Anxiety and Depression Scale, and the Patient Health Questionnaire–9 was satisfactory ( r > .74). Confirmatory factor analysis results supported the one-factor model. When compared with the gold standard, sensitivity and specificity were 93% and 73% for DMI-18 and 87% and 74% for DMI-10, respectively. Thus, both the versions are acceptable measures that can be used by nonpsychiatric professionals to detect affective comorbidities in their patients.